Copper oxide catalyst as well as preparation method and application thereof
By quenching rare earth metal salt solution on the surface of nano-copper oxide particles to form Ce/CuO-Q catalyst, the problem of poor thermal stability of copper-based catalysts is solved, achieving a highly efficient methanol-to-hydrogen reaction, improving catalytic activity and reducing CO selectivity.
Patent Information
- Application Number
- CN202411524104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing copper-based catalysts suffer from poor thermal stability in methanol steam reforming reactions, and traditional preparation methods are complex and difficult to apply on a large scale.
By quenching rare earth metal salt solution on the surface of nano-copper oxide particles, rare earth metal oxide coating and oxygen vacancies are introduced to form Ce/CuO-Q catalyst, thereby improving the thermal stability and activity of the catalyst.
The preparation of a highly efficient and low-cost nano-copper oxide catalyst was achieved, which improved the catalytic performance of the methanol-to-hydrogen reaction, extended the catalyst's running time, and reduced CO selectivity.
Smart Images

Figure CN119258876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a copper oxide catalyst. Background Art
[0002] The increasing energy consumption and environmental pollution caused by the use of fossil fuels have prompted the development of eco-friendly renewable energy strategies worldwide. Hydrogen has attracted increasing research attention as a next-generation energy source, but the high production and transportation costs have severely restricted its widespread application. Liquid methanol is considered to be a promising hydrogen carrier with inherent advantages in terms of safety and transportation economy. In addition, CH3OH has the advantages of high volumetric energy density and renewability, so low-cost in-situ hydrogen utilization can be achieved in fuel cell systems. Therefore, the development of efficient methanol-to-hydrogen reactions is of great significance to alleviate environmental problems and energy crises. Methanol steam reforming (MSR) is the most developed and commonly used method, mainly involving methanol decomposition and water gas shift reaction, because it has the advantages of high H / C molar ratio, no sulfur and nitrogen emissions, and low reforming temperature (200-350℃). The development of efficient and durable catalysts is of great significance for MSR reactions. Copper-based catalysts have attracted increasing attention due to their advantages such as low cost, high activity and H2 selectivity.
[0003] However, due to the low Taman temperature of copper (407 °C), active copper is prone to agglomeration and sintering during the reaction, so improving the thermal stability of copper-based catalysts is also an important issue.
[0004] Typically, impregnation, sol-gel, and co-precipitation methods are used to prepare copper-based nanocatalysts for various thermocatalytic reactions. These methods can control the atomic-scale composition and morphology of the catalyst surface to a certain extent. However, many strategies involve rather complicated preparation processes, such as harsh synthesis conditions (pressure, gas environment, etc.), specific solvents, and laborious modification treatments (annealing, ion exchange, or etching), which create obstacles for large-scale applications. In view of this, it is imperative to develop a simple, universal, and low-cost technology to achieve efficient surface engineering and improve the catalytic performance of MSR catalysts. Summary of the invention
[0005] The first object of the present invention is to provide a nano copper oxide catalyst with high catalytic activity and high selectivity.
[0006] The second object of the present invention is to provide a method for preparing the nano copper oxide catalyst.
[0007] The third object of the present invention is to provide application of the nano copper oxide catalyst in the field of alcohol reforming hydrogen production.
[0008] The present invention is achieved through the following technical solutions.
[0009] A nano copper oxide catalyst is prepared by quenching nano copper oxide particles at a temperature of 500-600°C in a rare earth metal salt solution, so that the rare earth metal oxide is coated on the surface of the nano copper oxide particles, and the rare earth metal ions enter the copper oxide lattice on the surface of the nano copper oxide particles, and the Cu in the copper oxide lattice is 2+ Reduced to Cu + The result is that the relative abundance of oxygen vacancies on the surface of the nano-copper oxide particles increases.
[0010] The rare earth metal salt solution includes a soluble salt solution of Ce, a soluble salt solution of La, a soluble salt solution of Y, a soluble salt solution of Nd or a soluble salt solution of Gd.
[0011] The particle size of the nano copper oxide particles is 20-50 nm.
[0012] The soluble salt of Ce includes cerium nitrate, cerium chloride or cerium sulfate;
[0013] The soluble salt of La includes lanthanum nitrate, lanthanum chloride or lanthanum sulfate;
[0014] The soluble salt of Y includes yttrium nitrate, yttrium chloride or yttrium sulfate;
[0015] The soluble salt of Nd includes neodymium nitrate, neodymium chloride or neodymium sulfate;
[0016] The soluble salt of Gd includes gadolinium nitrate, gadolinium chloride or gadolinium sulfate.
[0017] The relative abundance of oxygen vacancies on the surface of the nano copper oxide catalyst is 45%-46%.
[0018] The concentration of the rare earth metal salt solution is 0.25-0.35M.
[0019] A method for preparing a nano copper oxide catalyst comprises the following steps:
[0020] The nano copper oxide particles are heat treated and then quenched in a rare earth metal salt solution, and then the product is collected and dried to obtain the nano copper oxide particles. The mass volume ratio of the nano copper oxide particles to the rare earth metal salt solution is 1.3-1.6 g: 25 mL.
[0021] The temperature of the heat treatment is 500-600°C;
[0022] The heating rate of the heat treatment is 5-6°C / min;
[0023] The heat treatment time is 2-3h.
[0024] The drying temperature is 60-70°C;
[0025] The drying time is 10-12 hours.
[0026] An application of the nano copper oxide catalyst is to produce hydrogen by reforming alcohol;
[0027] The alcohols include C1-C5 alcohols.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The nano copper oxide catalyst provided by the present invention introduces cerium dioxide (CeO2) as a reforming promoter for alcohol by quenching. Quenching in a rare earth metal salt solution can allow rare earth metal ions to enter the copper oxide lattice on the surface of the nano copper oxide particles, so that the surface of the nano copper oxide particles causes defects to form on the catalyst surface, thereby introducing more oxygen vacancies. The presence of these oxygen vacancies can accelerate the dissociation of H2O, thereby promoting MSR reaction and reducing CO concentration. On the other hand, since the rare earth metal oxide loaded on the surface of the nano copper oxide particles after quenching has the effect of a physical barrier, agglomeration and sintering between Cu species in the reaction process are effectively prevented, and the thermal stability of the Cu-based catalyst is improved.
[0030] The preparation method of the nano copper oxide catalyst provided by the invention is simple, universal and low-cost, can realize efficient surface engineering and improve the catalytic performance of the prepared nano copper oxide catalyst.
[0031] The nano copper oxide catalyst provided by the invention can be applied to the efficient and highly selective reforming of alcohol to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of the MSR reaction is shown;
[0033] Figure 2a A schematic diagram of the quenching process of the nano copper oxide catalyst is shown;
[0034] Figure 2b XRD patterns of CuO-R, Ce / CuO-R and Ce / CuO-Q are shown;
[0035] Figure 2c Raman images of CuO-R, Ce / CuO-R and Ce / CuO-Q are shown;
[0036] Figure 2d TEM images of Ce / CuO-Q are shown;
[0037] Figure 2e shows the ADF-STEM image of Ce / CuO-QHA;
[0038] Figure 2fshows the ADF-STEM image of Ce / CuO-QHA;
[0039] Figure 2g shows the STEM-EDX image of Ce / CuO-Q;
[0040] Figure 2h The Cu element distribution map in STEM-EDX of Ce / CuO-Q is shown;
[0041] Figure 2i The O element distribution map in STEM-EDX of Ce / CuO-Q is shown;
[0042] Figure 2j The Ce element distribution map in STEM-EDX of Ce / CuO-Q is shown;
[0043] Figure 3 a shows an enlarged view of the XRD patterns of CuO-R, Ce / CuO-R and Ce / CuO-Q;
[0044] Figure 3 b shows the enlarged images of the Raman images of CuO-R, Ce / CuO-R and Ce / CuO-Q;
[0045] FIG4 shows SEM images of CuO-R, Ce / CuO-R and Ce / CuO-Q; wherein, Figure 4a SEM images of CuO-R, are shown; Figure 4b shows the SEM image of Ce / CuO-R; Figure 4c shows the SEM image of Ce / CuO-Q;
[0046] Figure 5 a shows the TEM image of Ce / CuO-R;
[0047] Figure 5 b shows the STEM-EDX image of Ce / CuO-R;
[0048] Figure 5 c shows the Cu element distribution map in STEM-EDX of Ce / CuO-R;
[0049] Figure 5 d shows the O element distribution map in STEM-EDX of Ce / CuO-R;
[0050] Figure 5 e shows the Ce element distribution map in STEM-EDX of Ce / CuO-R;
[0051] Figure 6 a shows graphs of CuO-R, Ce / CuO-R and Ce / CuO-Q;
[0052] Figure 6 b shows the quantitative results of oxygen vacancies of CuO-R, Ce / CuO-R and Ce / CuO-Q
[0053] Figure 6 b shows the XPS graphs of CuO-R, Ce / CuO-R and Ce / CuO-Q;
[0054] Figure 6 c shows the O1S diagrams of Ce / CuO-R and Ce / CuO-Q;
[0055] Figure 6 d shows the Cu2p diagram of Ce / CuO-R and Ce / CuO-Q;
[0056] Figure 6 e shows the Cu LMM AES patterns of Ce / CuO-R and Ce / CuO-Q;
[0057] Figure 6 f shows the Ce3d diagram of Ce / CuO-R and Ce / CuO-Q;
[0058] Figure 7 Shown are (a) XRD patterns, (b) Cu 2p XPS spectra, and (c) Cu LMM AESspectra of the catalysts after 10h of the reforming reaction.
[0059] Figure 8 shows the O1s XPS graphs of CuO-R, Ce / CuO-R and Ce / CuO-Q after 10 hours of reforming reaction;
[0060] Fig. 9 a shows the conversion rate of methanol to CuO-R, Ce / CuO-R and Ce / CuO-Q at different temperatures;
[0061] Fig. 9 b shows the selectivity of CuO-R, Ce / CuO-R and Ce / CuO-Q to CO at different temperatures;
[0062] Fig. 9 c shows the conversion rate of hydrogen of CuO-R, Ce / CuO-R and Ce / CuO-Q at different temperatures;
[0063] Fig. 9 d shows the catalytic effect of Ce / CuO-Q at steady state; the reaction conditions are 4 mL / h, and the molar ratio of H2O to CH3OH is 1.05;
[0064] Fig.10 a shows the steady-state catalytic diagram of Ce / CuO-Q;
[0065] Fig.10 b shows the steady-state catalytic diagram of La / CuO-Q;
[0066] Fig.10 c shows the steady-state catalytic diagram of Y / CuO-Q;
[0067] Fig.10 d shows the steady-state catalytic diagram of Nd / CuO-Q;
[0068] Fig.10 e shows the steady-state catalytic diagram of Gd / CuO-Q;
[0069] Fig.10 f shows the selectivity of MSR reaction of La / CuO-Q, Y / CuO-Q, Nd / CuO-Q and Gd / CuO-Q to CO; wherein the reaction conditions are 4 mL / h, and the molar ratio of H2O to CH3OH is 1.05;
[0070] Fig.11 The FTIR graphs of Ce / CuO-Q after reforming reaction for different time periods are shown;
[0071] Fig.12 a shows the FE-SEM image of Ce / CuO-Q;
[0072] Fig.12 b shows the FE-SEM image of U-Ce / CuO-Q;
[0073] Fig.12 c shows the Raman images of Ce / CuO-Q and U-Ce / CuO-Q. DETAILED DESCRIPTION
[0074] The present invention is further described below in conjunction with specific embodiments.
[0075] Example 1
[0076] CuO nanoparticles with a particle size of 100 nm were calcined at 550°C for 2 hours (heating rate: 5°C / min), and the amount of copper oxide added was 1.5 g, and then immersed in 25 mL of Ce(NO3)3 (0.3M) solution for quenching. After magnetic stirring for 5 minutes, the product was collected by centrifugation several times and dried in a forced air drying oven at 60°C for 12 hours. The nano copper oxide catalyst prepared in Example 1 is recorded as Ce / CuO-Q.
[0077] Comparative Example 1
[0078] 100 nm CuO nanoparticles were calcined at 550°C for 2 hours and then cooled naturally to room temperature. The CuO nanoparticles were then added to a Ce(NO3)3 solution, stirred, centrifuged, and finally dried. The catalyst prepared in Comparative Example 1 is labeled Ce / CuO-R.
[0079] Comparative Example 2
[0080] The 100 nm CuO nanoparticles were calcined at 550° C. for 2 hours and then cooled naturally to room temperature. The catalyst prepared in Comparative Example 2 was marked as CuO-R.
[0081] Meanwhile, in the present invention, the catalysts after 10 hours of MSR reaction are named R-CuO-R, R-Ce / CuO-R and R-Ce / CuO-Q, respectively, and the catalyst after 100 hours of reaction is marked as U-Ce / CuO-Q.
[0082] Inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis showed that the Ce contents in Ce / CuO-Q and Ce / CuO-R were 1.24 wt.% and 1.31 wt.%, respectively.
[0083] Example 2
[0084] CuO nanoparticles with a particle size of 100 nm were calcined at 550°C for 2 hours (heating rate: 5°C / min), and the amount of copper oxide added was 1.3 g, and then immersed in 25 mL of La(NO3)3 (0.3M) solution for quenching. After magnetic stirring for 5 minutes, the product was collected by centrifugation several times and dried in a forced air drying oven at 60°C for 12 hours. The nano copper oxide catalyst prepared in Example 2 is recorded as La / CuO-Q.
[0085] Example 3
[0086] CuO nanoparticles with a particle size of 100 nm were calcined at 550°C for 2 hours (heating rate: 5°C / min), and the amount of copper oxide added was 1.6 g, and then immersed in 25 mL of Y(NO3)3 (0.3M) solution for quenching. After magnetic stirring for 5 minutes, the product was collected by centrifugation several times and dried in a forced air drying oven at 60°C for 12 hours. The nano copper oxide catalyst prepared in Example 3 is recorded as Y / CuO-Q.
[0087] Example 4
[0088] CuO nanoparticles with a particle size of 100 nm were calcined at 550°C for 2 hours (heating rate: 5°C / min), and the amount of copper oxide added was 1.5 g, and then immersed in 25 mL of Nd(NO3)3 (0.3M) solution for quenching. After magnetic stirring for 5 minutes, the product was collected by centrifugation several times and dried in a 60°C forced air drying oven for 12 hours. The nano copper oxide catalyst prepared in Example 4 is recorded as Nd / CuO-Q.
[0089] Example 5
[0090] CuO nanoparticles with a particle size of 100 nm were calcined at 550°C for 2 hours (heating rate: 5°C / min), and the amount of copper oxide added was 1.5 g, and then immersed in 25 mL of Gd(NO3)3 (0.3M) solution for quenching. After magnetic stirring for 5 minutes, the product was collected by centrifugation several times and dried in a forced air drying oven at 60°C for 12 hours. The nano copper oxide catalyst prepared in Example 5 is recorded as Gd / CuO-Q.
[0091] The present invention uses a quenching method to perform cerium functionalization on the surface of CuO nanoparticles to form a Ce / CuO-Q catalyst rich in Ce single atom sites and some ultrafine CeO2 particles. Quenching CuO in a Ce(NO3)3 solution can promote Ce doping into the CuO lattice and generate abundant surface vacancies, thereby adjusting the local electronic structure and coordination environment of the catalyst surface. Ce ions in the lattice tend to be in the Ce 4+ and Ce 3+ , thereby further generating more oxygen vacancies. At the same time, the ultrafine CeO2 particles on the CuO surface can effectively inhibit the sintering and agglomeration of Cu materials during the MSR process, thereby extending the operating time of the catalyst. Compared with the reference catalyst (Ce / CuO-R) prepared by the traditional impregnation method, Ce / CuO-Q exhibits higher catalytic activity and lower CO selectivity in MSR, with a methanol conversion rate of 100% and a CO selectivity of 0.052% at 260°C. It is worth noting that the quenching method is also applicable to other rare earth salt solution systems, such as La / CuO-Q, Y / CuO-Q, Nd / CuO-Q and Gd / CuO-Q catalysts. Therefore, the method provided by the present invention provides a novel, simple and low-cost approach for the preparation of high-performance MSR catalysts.
[0092] In the present invention, the MSR reaction is measured in a continuous plug flow quartz reactor (eg Figure 1As shown). Before the test, a mixture consisting of an appropriate amount of SiO2 and 300 mg of catalyst was pressed into a sheet and then placed in the reforming chamber. A methanol aqueous solution with a H2O / CH3OH molar ratio of 1.05 entered the evaporation chamber through a Chuangrui CT1000 peristaltic pump (China). The reactor effluent (such as H2, CO2 and CO) was separated by a phase separator and analyzed using an SP-7890 gas chromatograph (China) equipped with TCD and FID. The gas flow rate was determined by a SCal Plus electronic soap bubble flowmeter (China), and the unreacted reactants were collected by a condensing device. The methanol conversion rate and gas product selectivity were evaluated according to the following formula.
[0093]
[0094]
[0095] What do the symbols represent?
[0096] The methanol conversion rate and gas product selectivity were evaluated according to the formula (Formula 1-4). MeOH Represents methanol conversion rate. H2 , S CO , S CO2 Represents the selectivity of H2, CO and CO2 respectively. i is the molar flow rate of component i in the gas. The quenching process of the Ce / CuO-Q catalyst prepared in the present invention is as follows: Figure 2a As shown. The present invention explored the composition of the catalyst by XRD analysis. Only the diffraction peak of CuO (PDF#80-1917) was detected in all catalysts ( Figure 2b ). Due to the low Ce loading and high dispersion, no Ce-related peaks were detected. The CuO peak of the Ce / CuO-Q catalyst was slightly shifted to a higher angle compared to the other samples ( Figure 3 a), which indicates that Ce is incorporated into the CuO lattice. 3+ ions. Raman spectroscopy further verified the structure of the catalyst. 223 and 613 cm -1 The peaks near 277 cm correspond to the stretching vibration of the Cu-O bond, while the peaks at 277 cm -1 The peaks near the Cu-O bond belong to the bending vibration ( Figure 2c ). It is worth noting that compared with CuO-R and Ce / CuO-R, Ce / CuO-Q has a -1 The peak near the Figure 3 b), which indicates that quenching in Ce(NO3)3 solution changes the Cu-O coordination environment, resulting in a defect-rich structure.
[0097] Scanning electron microscopy showed no significant difference in the basic morphology of CuO-R, Ce / CuO-R, and Ce / CuO-Q catalysts (Figure 4), indicating that quenching did not affect the overall morphology. The morphology and composition of the catalysts were further investigated using TEM with condenser spherical aberration correction. The surfaces of Ce / CuO-Q and Ce / CuO-R were decorated with ultrafine nanoparticles ( Figure 2d and Figure 5 a). In addition, N2 adsorption-desorption experiments were carried out on the catalysts to determine the texture characteristics of the catalysts. As shown in Table 1, the specific surface areas of CuO-R, Ce / CuO-R and Ce / CuO-Q are 16.3, 21.4 and 22.8 m 2 / g.
[0098] Table 1
[0099] Catalyst <![CDATA[S BET (m 2 g -1 )]]> <![CDATA[Pore volume(cm 3 g -1 )]]> Average pore size(nm) CuO-R 16.3 0.094 20.6 Ce / CuO-R 21.4 0.085 14.8 Ce / CuO-Q 22.8 0.051 8.6 U-Ce / CuO-Q 13.6 0.054 14.5
[0100] The increase in specific surface area further proves that ultrafine nanoparticles are generated on the CuO surface. From the elemental spectra of Ce / CuO-Q and Ce / CuO-R ( Figure 2g -j and Figure 5 be) It can be found that Ce species are distributed on the CuO surface. For the Ce / CuO-Q catalyst, the lattice spacing of 0.234nm for large particles is considered to be the CuO(111) plane, while the lattice spacing of 0.311nm for ultrafine nanoparticles corresponds to the CeO2(111) plane ( Figure 6 e). Importantly, the HAADF-STEM image of Ce / CuO-Q shows the presence of single Ce atoms ( Figure 1 f) indicates that part of Ce 3+ Therefore, these results collectively indicate that some changes in the CuO structure occurred in the quenched-derived Ce / CuO-Q compared with Ce / CuO-R, including the incorporation of Ce and the introduction of defects.
[0101] Unpaired electrons and defects are quantified by EPR ( Figure 6 a) All samples observed obvious isotropic resonance at g = 2.003, which is attributed to the unpaired electrons trapped in the oxygen vacancies. In addition, the quantitative results of the EPR signal intensity are shown in Figure 6 b. Oxygen vacancy concentration of Ce / CuO-Q (8.11×1015 spin g -1 ) are CuO-R(5..14×10 15 Spin g -1 ) and Ce / CuO-R (6.74×10 15 Spin g -1) by 1.58 and 1.20 times of that in Ce(NO3)3 solution. This result indicates that more oxygen vacancies are generated by quenching in Ce(NO3)3 solution.
[0102] In order to explore the chemical changes caused by quenching, XPS spectroscopy was performed on the samples. The O1sXPS spectra of the three samples can be decomposed into a combination of lattice oxygen (OL, ~529.7eV), oxygen vacancies (OV, ~531.6eV) and surface chemically adsorbed oxygen (OC, ~533.3eV) ( Figure 2c ). It is worth noting that the relative abundance of OV of Ce / CuO-Q (45.9%) is higher than that of CuO-R (37.6%) and Ce / CuO-R (40.8%). In the Cu2p3 / 2XPS spectrum ( Figure 6 In d), the peak at 945-938 eV is assigned to Cu 2+ The Cu2p3 / 2 peak of Ce / CuO-Q (933.4 eV) moves to a lower binding energy than the Cu2p3 / 2 peak of Ce / CuO-R (933.5 eV), which means that the quenching process reduces the Cu 2+ The valence state of Cu species was further verified using CuLMM spectroscopy ( Figure 6 e). The peaks at 917.9 and 916.3 eV are respectively related to Cu 2+ and Cu + The Cu of Ce / CuO-Q + / (Cu + +Cu 2+ ) ratio (25.9%) is higher than that of Ce / CuO-R + / (Cu + +Cu 2+ ) ratio (20.6%), which is related to the results of Cu2p3 / 2XPS. In addition, the Ce3d5 / 2XPS spectrum was fitted into three peaks ( Figure 6 f), where v and v' are determined as Ce 4+ ions, v' corresponds to Ce 3+ ions. Compared with Ce / CuO-R, all peaks of Ce / CuO-Q shifted to higher binding energies. 3+ / (Ce 3+ +Ce 4+ ) decreased from 32.4% to 27.1% (Table 2).
[0103] Table 2
[0104]
[0105] This indicates that quenching induces Cu 2+ To Cu +The electron conversion is accompanied by Ce 3+ To Ce 4+ Therefore, quenching in Ce(NO3)3 solution can change the electronic structure and surface properties of CuO nanoparticles, resulting in oxygen-rich vacancies. This is beneficial to the activation of H2O and the conversion of C-containing intermediates, thereby improving the catalytic activity and CO2 selectivity of the MSR reaction.
[0106] The catalyst was studied by XRD, XPS and XAES after 10 hours of reforming reaction. Figure 7 In a), diffraction peaks of metallic copper (PDF#04-0836) and Cu2O (PDF#77-0199) were detected, indicating that CuO was reduced to metallic copper and Cu2O. Similarly, no diffraction peaks related to Ce were observed. In addition, the Cu2p3 / 2 spectrum was fitted into four peaks ( Figure 7 b). The peak at around 932.9 eV corresponds to Cu + or Cu, and the peak at ~934.8eV is similar to Cu 2+ Related. 2+ The appearance of Cu2p3 / 2 spectrum may be due to the oxidation of the catalyst surface during the test. + The binding energy of Cu is very close to that of Cu and is difficult to distinguish. Therefore, the CuLMM spectrum is used to further verify the valence state of the Cu species. The CuLMM spectrum of the catalyst is decomposed into six peaks ( Figure 7 c). The three peaks located near 918.8, 917.7 and 916.5 eV represent Cu, Cu 2+ and Cu + It is worth noting that the Cu + The peak area ratio (39.5%) is higher than that of R-Ce / CuO-R + Peak area ratio (35.5%) (Table 3)
[0107] Table 3
[0108]
[0109] This means that the quenching-induced synergistic effect between Cu and Ce species in the catalyst is enhanced, thereby promoting the MSR reaction. The oxygen vacancy concentration on the catalyst surface was further investigated by O1s XPS spectroscopy ( Figure 8 The Ov peak area ratios are R-Ce / CuO-Q (80.6%) > R-Ce / CuO-R (75.2%) > R-CuO-R (67.1%), which indicates that the quenching-induced catalysts contain more oxygen vacancies during the reaction.
[0110] MSR tests were performed to evaluate the performance of different catalysts. Since the reaction is endothermic, the methanol conversion and CO selectivity increase with increasing temperature. Taking the methanol conversion at a reforming temperature of 260°C as an indicator, it was found that the order of catalytic activity was Ce / CuO-Q (100%) > Ce / CuO-R (92.1%) > CuO-R (82.7%) accompanied by a CO selectivity order of Ce / CuO-Q (0.052%) < Ce / CuO-R (0.072%) < CuO-R (0.086%) ( Fig. 9 ab), indicating that quenching in Ce(NO3)3 solution can improve activity and reduce CO content due to the increase in defects and the interaction between Ce species and CuO. The catalyst has a H2 selectivity of about 75%, which meets its stoichiometric value and can provide sufficient hydrogen for fuel cells ( Fig. 9 c). Considering the excellent performance of Ce / CuO-Q in the test, the powder was mixed with aluminum sol to make a slurry for coating cordierite honeycomb ceramics. Subsequently, durability tests were carried out at 260°C. During the 100-hour operation, no obvious deactivation was observed ( Fig. 9 d). The methanol conversion rate dropped to 92.3%, and the CO selectivity was between 0.042% and 0.059%, which showed that the structured Ce / CuO-Q catalyst had good stability. It is worth noting that the catalytic performance of the structured Ce / CuO-Q catalyst was not significantly different from that of the Ce / CuO-Q catalyst ( Fig.10 a). In addition, the catalytic performance of the quenched-derived catalysts in MSR is superior to that of the copper-based catalysts reported in the literature in Table 4).
[0111] Table 4
[0112]
[0113] The literature involved in Table 4 is as follows:
[0114] [1] F. Bossola, T. Roongcharoen, M. Codurii, C. Evangelisti, F. Somodi, L. Sementa, A. Fortunelli, V. Dal Santo, Discovering indium as hydrogen productionbooster for a Cu / SiO2 catalyst in steam reforming of methanol, AppliedCatalysis B: Environmental 297(2021)120398.
[0115] [2]Y.Chen,S.Li,S.Lv,Y.Huang,A novel synthetic route for MOF-derivedCuO-CeO2 catalyst with remarkable methanol steam reforming performance,Catalysis Communications 149(2021)106215.
[0116] [3]X.Jia,H.Zhang,B.Ren,J.Xie,P.Ge,B.Zhang,Fe–Ni–Ce–Zr-modified CuO–ZnO catalyst for methanol steam reforming,Journal of the Energy Institute 110(2023)101316.
[0117] [4]H.Shahsavar,M.Taghizadeh,A.D.Kiadehi,Effects of catalystpreparation route and promoters(Ce and Zr)on catalytic activity of CuZn / CNTscatalysts for hydrogen production from methanol steam reforming,InternationalJournal of Hydrogen Energy 46(13)(2021)8906-8921
[0118] [5]A.M.Kovalskii,A.T.Matveev,Z.I.Popov,I.N.Volkov,E.V.Sukhanova,A.A.Lytkina,A.B.Yaroslavtsev,A.S.Konopatsky,D.V.Leybo,A.V.Bondarev,I.V.Shchetinin,K..L.Firestein,D.V.Shtansky,D.V.Golberg,(Ni,Cu) / hexagonal BNnanohybrids–New efficient catalysts for methanol steam reforming and carbonmonoxide oxidation,Chemical Engineering Journal 395(2020)125109.
[0119] [6]S.Yang,F.Zhou,Y.Liu,L.Zhang,Y.Chen,H.Wang,Y.Tian,C.Zhang,D.Liu,Morphology effect of ceria on the performance of CuO / CeO2 catalysts forhydrogen production by methanol steam reforming,International Journal ofHydrogen Energy 44(14)(2019)7252-7261.
[0120] [7]Y.Chen,Y.Huang,Influence of ceria existence form on deactivationbehaviorr of Cu-Ce / SBA-15catalysts for methanol steam reforming,InternationalJournal of Hydrogen Energy 48(4)(2023)1323-1336.
[0121] [8]S.Qian,H.Liu,Y.Wang,D.Mei,Structural optimization of 3D printedSiC scaffold with gradient pore size distribution as catalyst support formethanol steam reforming,Fuel 341(2023)127612.
[0122] [9]O.O.Fasanya,A.Y.Atta,M.T.Z.Myint,J.Dutta,B.Y.Jibril,Effects ofsynthesis methods on performance of CuZn / MCM-41catalysts iin methanol steamreforming,International Journal of Hydrogen Energy 46(5)(2021)3539-3553.
[0123]
[10] C.Li,S.Yuan,X.Yao,X.Yu,B.Li,S.-T.Tu,Structured nanoporous coppercatalysts prepared by laser powder bed fusion and dealloying for on-boardmethanol steam reforming,Fuel 347(2023)128367.
[0124]
[11] Y.Wang,H.Liu,D.Mei,S.Yu,Direct ink writing of 3D SiC scaffold ascatalyst support for thermally autonomous methanol steam reformingmicroreactor,Renewable Energy 187(2022)923-932.
[0125]
[12] E.Baydir, Aras, Methanol steam reforming in a microchannelreactor coated with spray pyrolysis method for durable Cu / ZnO nanocatalyst, Journal of Analytical and Applied Pyrolysis158(2021)105278.
[0126] Importantly, the MSR performance of CuO nanoparticles quenched in other rare earth salt solutions (La, Y, Nd, and Gd) was also investigated. Under the same reaction conditions, the quenched catalysts showed higher catalytic activity and lower CO selectivity than CuO-R and Ce / CuO-R. Fig.10 bf), which verifies the versatility of the quenching method for preparing catalysts.
[0127] The MSR reaction pathways on the copper-based catalysts were mainly based on three hypothetical pathways with methyl formate (CH3OOCH*), carbon monoxide (CO*), and methyl formate (HCOO*) as surface intermediates. Therefore, the generation pathways of Ce / CuO-Q catalyst at 260 °C were further elucidated by Fourier transform infrared spectroscopy (FTIR). Fig.11 ). 3425cm -1 and 1603cm -1 The peak at represents the strong absorption peak of H2O. The stretching vibration peak and symmetric bending peak of methanol-derived OH bond are located at 3850-3700cm -1 and 1450cm -1 The CH bond stretching in the methoxy group (C3O*) is located at 2922 cm -1 and 2854cm -1 The CO stretch peak in CH3O* is located at 1150-1000cm -1 .2968cm -1 、1558cm -1 and 1385cm -1 The peak at about 1730 cm represents the CH stretching vibration of formate and the asymmetric and symmetric stretching of OCO. -1 The peak at is the C=O oscillation peak of aldehydes (CH2O*), and the absorption peak of CO2 is concentrated at 2400-2300cm -1 In addition, as the reaction time increases, the -1 、2400-2300cm -1 、1730cm -1 and 558cm -1The peak intensity at increases continuously, indicating that CH3O*, CO2, CH2O*, and HCOO* gradually accumulate on the catalyst surface. It is worth noting that these peak signals will remain stable after 9 minutes, which means that the adsorption of reactants and intermediates on the catalyst surface has reached saturation. The results show that CH3OH is converted into CH3O*, CH2O*, and HCOO* in sequence, and HCOO* eventually decomposes into H2 and CO2, where CH2O* reacts with OH* or O* from H2O to generate HCOO*. Fig.11 There is no CO peak in the results, which indicates that the CO content is lower than the detection limit of infrared. It can be seen that the Ce / CuO-Q catalyst provided by the present invention can effectively inhibit the generation of CO in the catalytic process.
[0128] Particle sintering aggregation and carbon deposition can lead to the deactivation of copper-based catalysts during the MSR reaction. Scanning electron microscopy and Raman spectroscopy were performed on Ce / CuO-Q and U-Ce / CuO-Q catalysts. The results showed that the particle size of U-Ce / CuO-Q was significantly larger than that of Ce / CuO-Q ( Fig.12 ab). At the same time, the specific surface area of the catalyst used was increased from 22.8m 2 / g is reduced to 3.6m 2 / g
[0129] In addition, there is no D band (1300-1400cm -1 , disorder and defects) and G band (1500-1600cm -1 , graphite or well-structured) peak ( Fig.12 c). Therefore, the sintering and agglomeration of particles lead to the decrease of the activity of Ce / CuO-Q, which may be caused by Ostwald ripening, nanoparticle migration and agglomeration during the reaction.
[0130] In summary, the present invention provides a quenching method to regulate the local electronic structure and coordination environment on / near the catalyst surface by inducing Ce doping and generating vacancies on the CuO surface. At the same time, the ultrafine CeO2 particles on the CuO surface can effectively prevent the sintering growth of Cu species during the MSR process, thereby extending the operation time of the catalyst. Compared with the reference catalyst (Ce / CuO-R) prepared by the traditional impregnation method, Ce / CuO-Q achieved a methanol conversion of 100% at 260°C and a CO selectivity of 0.052%, showing higher catalytic activity and lower CO selectivity in the reforming process. After 100 hours of operation, the methanol conversion of the structured Ce / CuO-Q catalyst dropped to 92.3%, and the CO selectivity was 0.042%-0.059%, indicating that the catalyst has good catalytic durability. In addition, Fourier transform infrared spectroscopy also elucidated the evolution of reactants and intermediates on the catalyst surface. The sintering and agglomeration of Ce / CuO-Q led to the deactivation of the catalyst during the reaction. This quenching method is also applicable to other rare earth salt solution systems, including La / CuO-Q, Y / CuO-Q, Nd / CuO-Q and Gd / CuO-Q catalysts.
Claims
1. A nano copper oxide catalyst, characterized in that: The nano copper oxide particles are quenched in a rare earth metal salt solution at a temperature of 500-600°C, so that the rare earth metal oxide is coated on the surface of the nano copper oxide particles, and the rare earth metal ions enter the copper oxide lattice on the surface of the nano copper oxide particles, and the Cu in the copper oxide lattice is 2+ Reduced to Cu + The result is that the relative abundance of oxygen vacancies on the surface of the nano-copper oxide particles increases.
2. The nano copper oxide catalyst according to claim 1, characterized in that: The rare earth metal salt solution includes a soluble salt solution of Ce, a soluble salt solution of La, a soluble salt solution of Y, a soluble salt solution of Nd or a soluble salt solution of Gd.
3. The nano copper oxide catalyst as claimed in claim 1, characterized in that: The particle size of the nano copper oxide particles is 20-50 nm.
4. The nano copper oxide catalyst according to claim 1, characterized in that: The soluble salt of Ce includes cerium nitrate, cerium chloride or cerium sulfate; The soluble salt of La includes lanthanum nitrate, lanthanum chloride or lanthanum sulfate; The soluble salt of Y includes yttrium nitrate, yttrium chloride or yttrium sulfate; The soluble salt of Nd includes neodymium nitrate, neodymium chloride or neodymium sulfate; The soluble salt of Gd includes gadolinium nitrate, gadolinium chloride or gadolinium sulfate.
5. The nano copper oxide catalyst according to claim 1, characterized in that: The relative abundance of oxygen vacancies on the surface of the nano copper oxide catalyst is 45%-46%.
6. The nano copper oxide catalyst according to claim 1, characterized in that: The concentration of the rare earth metal salt solution is 0.25-0.35M.
7. The method for preparing a nano copper oxide catalyst as claimed in claim 1, characterized in that: The steps include: The nano copper oxide particles are heat-treated and then quenched in a rare earth metal salt solution, and then the product is collected and dried to obtain the product.
8. The nano copper oxide catalyst according to claim 1, characterized in that: The mass volume ratio of nano copper oxide particles to rare earth metal salt solution is 1.3-1.6 g: 25 mL; The temperature of the heat treatment is 500-600°C; The heating rate of the heat treatment is 5-6°C / min; The heat treatment time is 2-3h.
9. The nano copper oxide catalyst according to claim 1, characterized in that: The drying temperature is 60-70°C; The drying time is 10-12 hours.
10. The use of the nano copper oxide catalyst as claimed in claim 1, characterized in that: Applied to the reforming of alcohol to produce hydrogen; The alcohols include C1-C5 alcohols.
Citation Information
Patent Citations
Hydrogen production catalyst
CN102513105A
Preparation method of copper-based rare earth catalyst for hydrogen production by methanol steam reforming
CN116173971A
Copper-zinc oxide catalyst and preparation method and application thereof
CN117531516A
Modified copper slag and preparation method and application thereof
CN118745522A
Process for producing exhaust treatment catalyst powders, and their use
US20090325792A1